Pelaksanaan Kegiatan Pembelajaran Model Reggio Emelio Pada Anak Usia 4 – 5 Tahun di RA Asysyubbani Hulaan - Menganti – Gresik - Umi Masturoh (AT-THUFULY : Jurnal Pendidikan Islam Anak Usia Dini, 2020)
The research of this study is to describe how the implementation of the learning activity model using the Reggio Emelio approach which is applied in RA Asysubbani Hulaan, Menganti District, Gresik Regency in group A children aged 4-5 years. This research was carried out for a long time, namely for 4 months starting in November 2019, the end of the first semester of the learning year and the beginning of the second semester in February 2020. The type of research used here is descriptive research with a qualitative approach, where the informant's task in this study is the teacher, who teaches in group B1 where the number of students is 21, consisting of 12 boys and 9 girls with the guidance of 1 teacher and parents of B1 group children RA Asysubbani Hulaan, Menganti District, Gresik Regency. Data collection techniques use observation, interviews and documentation, which later the data data will be analyzed using data analysis techniques Miles and Huberman by reducing data, for data presentation and drawing conclusions from the data obtained during the research implementation. Based on the results of this study, it can be concluded that: 1) The Daily Learning Implementation Plan (RPPH) made by educators has not shown an integrated activity which is not right with the theme or in other words, the learning model in RA Asysyubbani is still not observant in combining activities with sub themes on the specified day; ; (2) In the implementation of the Reggio Emelio model of learning activities in RA Asysubbani Hulaan, Menganti District, Gresik Regency, there is a finding that the implementation of learning activities carried out on children is quite good and appropriate according to PAUD children's learning; (3) The teacher's assessment of students does not appear to be based on an authentic assessment in the field; (4) The Reggio Emelio learning model at RA Asysubbani Menganti Gresik involves two main elements in education, namely teachers and guardians of students / parents, but the participation of parents is still low and the participation of the community around the unit or RA Asysubbani Hulaan Menganti Gresik also seems not visible. (From the research that was carried out for four months, it is suggested that the teaching staff at RA Asysubbani Hulaan Menganti Gresik need to be given or follow further training guidance, for example how to make an integrated and precise daily learning implementation plan or need to do further research with an action approach research so that in the future the results can be maximized and better results can be obtained.